Четвертинні відклади печери Буковинка та їх палеогеографічне значення - Рідуш, Богдан (Чернівецький університет, 2004)
The remains of Late Pleistocene fauna were found in the large gypsum cave Bukovynka (the middle part of the Prut River valley, Chernivtsi Region). The fauna list includes Coelodonta antiquitatis, Crocuta spelaea, Ursus spelaeus, Equus ferus, Bos primigenius, Cervus elaphus, Sus scrofa, Vulpes vulpes. Many bones have the marks of human activity and gnawing marks. The site is identified as a cave hyena den. It is dated by Wurm 2.
Keywords: cave sediments; Crocuta spelaea; cave hyena den; gypsum karst; Bukovynka Cave; MIS 3; cut marks